Immobilization and characterization of β-galactosidase from Aspergillus oryzae in polyvinyl alcohol hydrogels - Akdogan, Doruk; Peksel, Aysegul (WILEY, 2025)
One of the main goals of contemporary biotechnology has been the development of novel immobilized enzyme formulations. In the present study, the industrially important beta-galactosidase was trapped in a polyvinyl alcohol (PVA) gel to immobilize it. The optimization of immobilization method and characterization of the immobilized enzyme were studied. The results were compared with free enzymes. The results indicate that the optimal temperature range for the enzyme to be at following immobilization is between 40 degrees C and 50 degrees C. At pH 7, the optimal pH, the activity increased, the Vmax value increased from 1.936 to 2.495 U mg-1, and the Km value decreased from 4.861 to 0.982 mM. Depending on how stable the immobilized enzyme when stored, beta-galactosidases immobilized on PVA gels showed 52.87% activity at the end of the seventh week and 58.86% activity at the end of the fifth week. Their initial activity subsided after three reuses. The final result was 66%. Therefore, one may argue that it increases the catalytic effect of the enzyme. As a result, it has been found that immobilized beta-galactosidase has more potent enzymatic properties than free beta-galactosidase, which may make it more advantageous for industrial processes. Further studies could delve deeper into the mechanistic aspects of the immobilization process in an effort to improve optimization and tailor the immobilized enzyme to specific industrial needs.
Keywords: biocatalysis; encapsulation; enzyme stability; hydrogel matrix; LACTOSE; PERFORMANCE; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology